Cosmetic Syndrome Correction with Calcium Hydroxylapatite-Based Filler in Patients with Connective Tissue Dysplasia - Maria Shirshakova; Elena Morozova; Daria Sokolova; Svetlana Pervykh; Lyailya Kayumova (Hindawi Limited, 2021)
Undifferentiated connective tissue dysplasia is one of the most common diseases of nowadays, which does not fit into the group of hereditary syndromes. This condition is diagnosed in 20-50% of the population at any age. The study aimed to correct the facial soft tissues of patients with undifferentiated connective tissue dysplasia through the cosmetic procedure of calcium hydroxylapatite injection. In 2018, a 36-year-old patient addressed the beauty salon with signs of undifferentiated connective tissue dysplasia, such as severe asymmetry of the face, infraorbital and nasolabial sulci, and thin and easily folding skin. Signs were observed from the age of 22, i.e., for 14 years. The therapy was performed using special features of the correction of facial soft tissue changes in patients with connective tissue dysplasia (CTD) using calcium hydroxylapatite-based products (Radiesse®, Merz North America, Inc., USA). Particular attention is given to the need for early correction to prevent premature skin aging related to this condition. After 14 days, a significant improvement of the patient's skin condition was noted after the passing of two procedures. Her condition was estimated as consistent with T1-2P0G0A1Zh1 P1M1K1 and corresponded to grade I age-related changes in the superficial soft tissues. The performed treatment showed high efficacy in case of mild connective tissue dysplasia diagnosis. The results showed that when collecting information from anamnesis, the diagnostic criteria for dysplasia should be considered. If the criteria are met, the cosmetological correction with collagen stimulators becomes possible.